Mechanical Characteristics of Hardened Concrete with Different Mineral Admixtures: A Review. (29th January 2014) - Ayub, Tehmina; Khan, Sadaqat Ullah; Memon, Fareed Ahmed
Abstract : The available literature identifies that the addition of mineral admixture as partial replacement of cement improves the microstructure of the concrete (i.e., porosity and pore size distribution) as well as increasing the mechanical characteristics such as drying shrinkage and creep, compressive strength, tensile strength, flexural strength, and modulus of elasticity; however, no single document is available in which review and comparison of the influence of the addition of these mineral admixtures on the mechanical characteristics of the hardened pozzolanic concretes are presented. In this paper, based on the reported results in the literature, mechanical characteristics of hardened concrete partially containing mineral admixtures including fly ash (FA), silica fume (SF), ground granulated blast furnace slag (GGBS), metakaolin (MK), and rice husk ash (RHA) are discussed and it is concluded that the content and particle size of mineral admixture are the parameters which significantly influence the mechanical properties of concrete. All mineral admixtures enhance the mechanical properties of concrete except FA and GGBS which do not show a significant effect on the strength of concrete at 28 days; however, gain in strength at later ages is considerable. Moreover, the comparison of the mechanical characteristics of different pozzolanic concretes suggests that RHA and SF are competitive.